South Africa’s green bond market: financing sustainable development - Priviledge Cheteni; Herrison Matsongoni; Ikechukwu Umejesi (Cogent Economics & Finance)
Due to its potential and sustainable development goals, the green bond market has recently gained traction as a leeway for some businesses. A qualitative approach was used to solicit views and perceptions from 60 participants to gain insight into the market. The study employed a snowball sampling technique to select 60 participants in 10 focus groups, each accommodating 6 participants. Thematic analysis was employed to analyse data. Focus group discussions and thematic analysis of data allowed for an in-depth exploration of subjective experiences, perceptions, and interpretations of stakeholders. Eight key themes emerged from thematic analysis: awareness and education, regulatory frameworks, collaboration, project diversification, risk management, capacity building, impact measurement and innovation. These findings provide a holistic perspective on the critical factors influencing the success and growth of the green bond market. The study’s findings also highlighted the importance of raising awareness and education about the green bond market among stakeholders, including issuers, investors, and the general public.